2019
DOI: 10.1039/c9cy00532c
|View full text |Cite
|
Sign up to set email alerts
|

Tunable colloidal Ni nanoparticles confined and redistributed in mesoporous silica for CO2 methanation

Abstract: Colloidal Ni nanoparticles were prepared using seed-mediated strategies and encapsulated in mesoporous silica to yield stable and sinter-resistant hydrogenation catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 72 publications
2
26
0
Order By: Relevance
“…The deposition of dopants (i.e., ZrO 2 ) onto the catalyst surface [585] and the encapsulation of colloidal catalyst nanoparticles prevent the degradation process [586]. Further, the regeneration of the deactivated catalysts due to sintering and carbon deposition is practicable.…”
Section: Catalytic Methanationmentioning
confidence: 99%
“…The deposition of dopants (i.e., ZrO 2 ) onto the catalyst surface [585] and the encapsulation of colloidal catalyst nanoparticles prevent the degradation process [586]. Further, the regeneration of the deactivated catalysts due to sintering and carbon deposition is practicable.…”
Section: Catalytic Methanationmentioning
confidence: 99%
“…The encapsulated NiIJ4.4)@SiO 2 catalyst was characterized and discussed in more detail in earlier work (see ref. 49).…”
Section: Catalyst Synthesis and Characterizationmentioning
confidence: 99%
“…Our recent work reported that colloidal Ni nanoparticles (NiNPs) can be synthesized with sizes in the 3-8 nm range by employing a seed-mediated approach. 49 An effective strategy to support such NiNPs and obtain active hydrogenation catalysts was to encapsulate them in a silica (SiO 2 ) support grown around the NiNPs. Work by Pu et al highlighted the possibility of encapsulating Ni particles in supports other than SiO 2 including Al 2 O 3 , TiO 2 and CeO 2 , although the final particle sizes were significantly larger than those of conventional Ni-based hydrogenation catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ni(Col) and Ni(Pr)/Au@SiO 2 samples had to undergo reduction treatment at high temperature first. Temperature Programmed Reduction (TPR) of the colloidal Ni NPs [41] gave a required reduction temperature in H 2 of 450-600°C to fully reduce the passivated Ni NPs to their metallic phase. However, due to the limited stability of Au@SiO 2 at high temperatures and the practical limitations of the Linkam Cell brought about by the high heat capacity of H 2 , the maximum temperature that can be reliably achieved is 400°C.…”
Section: Introductionmentioning
confidence: 99%